2019
DOI: 10.1007/s00220-019-03504-6
|View full text |Cite
|
Sign up to set email alerts
|

Modularity of Relatively Rational Vertex Algebras and Fusion Rules of Principal Affine W-Algebras

Abstract: We study modularity of the characters of a vertex (super)algebra equipped with a family of conformal structures. Along the way we introduce the notion of rationality and cofiniteness relative to such a family. We apply the results to determine modular transformations of trace functions on admissible modules over affine Kac-Moody algebras and, via BRST reduction, trace functions on regular affine W -algebras. * 1We prove the following result as Theorem 5.12. In fact we derive it from the stronger but more techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Fusion rules of W-algebras are needed for the proof of the first main Theorem. They have been proven in the simply-laced case if a certain coprime property holds for the denominator of the level [32,33]. The proof was based on Verlinde's formula and I take the slightly different point of view that the map (2) is a ring isomorphism from the Grothendieck ring of the regular W-algebra to the endomorphism ring of the direct sum of all inequivalent simples (1).…”
Section: Fusion Rules Of W-algebrasmentioning
confidence: 99%
See 4 more Smart Citations
“…Fusion rules of W-algebras are needed for the proof of the first main Theorem. They have been proven in the simply-laced case if a certain coprime property holds for the denominator of the level [32,33]. The proof was based on Verlinde's formula and I take the slightly different point of view that the map (2) is a ring isomorphism from the Grothendieck ring of the regular W-algebra to the endomorphism ring of the direct sum of all inequivalent simples (1).…”
Section: Fusion Rules Of W-algebrasmentioning
confidence: 99%
“…Moreover it was shown that the Heisenberg coset is isomorphic to a regular W -algebra of type A. The proof relied on the fusion rules of regular W-algebras of type A and so in that work it could only be done if the coprime condition of [32,33] was satisfied. The exact same proof now works in general and so Corollary 1.…”
Section: Fusion Rules Of W-algebrasmentioning
confidence: 99%
See 3 more Smart Citations